HIV controllers: hope for a functional cure - Deng, Zhuoya; Yan, Hongxia; Lambotte, Olivier; Moog, Christiane; Su, Bin (Frontiers in Immunology, 2025)
Elite controllers (ECs) and post-treatment controllers (PTCs) represent important models for achieving a functional cure for HIV. This review synthesizes findings from immunological, genetic, and virological studies to compare the mechanisms underlying HIV suppression in ECs and PTCs. Although ECs maintain viral control without antiretroviral therapy (ART), PTCs achieve suppression following ART discontinuation. Both groups rely on adaptive and innate immunity, host genetic factors, and characteristics of the HIV reservoir; however, they exhibit distinct immune responses and genetic profiles. These differences provide insights into strategies for sustained ART-free remission. Understanding the shared and unique mechanisms in ECs and PTCs can inform the development of novel therapeutic approaches, including immune-based therapies and genome editing, to achieve a functional cure for HIV-1.